Application of Project Based Learning Models to Improve Student Learning Outcomes in Science Material - Pangkey, Yenny Anggraeni (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to determine the increase in learning outcomes in science learning through the application of the PjBL model. This research is a classroom action research with 21 students of grade VI SD Margadana 5 Tegal as the subject. This research was conducted in 3 cycles, each cycle of 2 meetings. Each meeting consists of 4 stages, namely planning, implementing, observing and reflecting. Based on the results of the research, in the first cycle, it was obtained an average of 68.09 classical student learning outcomes with 52% student completeness success, and in the second cycle the classical student learning outcomes were 70.47 with the completeness success increasing to 67% and still under the indicators of success. In cycle III, the classical average of student learning outcomes was 83.33 with the success of student completeness increasing to 86% in this case it was more than the 75% achievement indicator. So from cycle I, cycle II and cycle III there is an increase in student learning outcomes. So, in this study it can be concluded that using the PjBL model can improve student learning outcomes in science subjects magnetic and non-magnetic objects.